2020
DOI: 10.1186/s12916-020-01774-9
|View full text |Cite
|
Sign up to set email alerts
|

Preventable medication harm across health care settings: a systematic review and meta-analysis

Abstract: Background Mitigating or reducing the risk of medication harm is a global policy priority. But evidence reflecting preventable medication harm in medical care and the factors that derive this harm remain unknown. Therefore, we aimed to quantify the prevalence, severity and type of preventable medication harm across medical care settings. Methods We performed a systematic review and meta-analysis of observational studies to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 64 publications
5
57
0
5
Order By: Relevance
“…In line with previous research, 35,36 we found that the majority of the potentially serious DRPs was caused by drug selection problems, in particular inappropriate combinations of drugs, and involved mainly drugs from the nervous and cardiovascular systems. Furthermore, our top 10 most commonly involved drug subgroups corresponds with previous findings of common drugs causing hospitalisations, prolonged hospitalisations, life‐threatening conditions, and disability 37 .…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous research, 35,36 we found that the majority of the potentially serious DRPs was caused by drug selection problems, in particular inappropriate combinations of drugs, and involved mainly drugs from the nervous and cardiovascular systems. Furthermore, our top 10 most commonly involved drug subgroups corresponds with previous findings of common drugs causing hospitalisations, prolonged hospitalisations, life‐threatening conditions, and disability 37 .…”
Section: Discussionsupporting
confidence: 92%
“…Medication-related incidents, including medication errors (MEs) and adverse medication events (AMEs), are common in the perioperative setting. [1][2][3] Perioperative ME rates (4-11%) 1,2 are consistent with ME rates in other hospital areas, such as inpatient wards (5-19%) [4][5][6][7] and outpatient clinics (7-12%). [8][9][10] However, 10 to 13 medications are administered per operation, 1,11 resulting in a high percent of operations involving medication-related incidents.…”
Section: Background and Significancesupporting
confidence: 63%
“…6 A recent systematic review and meta-analysis reported that the highest prevalence of preventable harm due to medication was at the prescribing and monitoring stages of the medication use process, and psychotropic medication was among the most common therapeutic groups associated with preventable medication harm. 7 However, most medication safety research for patients with mental illness has focused on hospital settings, with little data available on prescribing safety in primary care for this population. 8 9 This is important as primary care is often the first point of contact for people with mental illness with ~90% of adults managed entirely in primary care, including those with high levels of need and complexity.…”
Section: Introductionmentioning
confidence: 99%